A Real-Time Hard X-Ray Tomographic System During Lower Hybrid Current Drive on HL-2A Tokamak. (18th August 2017) - Yuan, C.; Fan, W. W.; Zhao, Y. F.; Liu, Z. H.; Cao, J.; Yuan, G. L.; Yin, Z. J.
Abstract: A set of real-time tomographic systems for tokamak plasma hard X-ray (HXR) diagnosis was designed, which is dedicated to real-time investigation of X-ray energy and its density profile that are produced by fast electron bremsstrahlung emission between the energy span of 20 to 200 keV under the lower hybrid (LH)–driven mode of HL-2A device. By utilizing an integrated detector array of lutetium yttrium oxyorthosilicate scintillators and silicon photomultipliers, and in conjunction with high-speed main electronics and appropriate digital processing algorithms, this tomographic system has achieved real-time energy surveillance of HXR that are radiated from 12 different chords on the poloidal plane of the HL-2A plasma region. The temporal and spatial resolutions of this system are 10 ms and 2 cm, respectively. The real-time tomography of the investigation results can clearly display the spatial distribution and its evolution over time of HXR energy. Onsite HL-2A experiments have proven that this real-time tomographic system is qualified as a reliable platform in the research field of plasma state and high-energy particles energy during LH current mode.